Strategi Komunikasi Internal dalam Transformasi Identitas Organisasi: Studi Kasus PT Pantau Sumber Berita dari Media Online Menuju Content Creator Berbasis Media Sosial - Aditya Andreas; Agung Sukariman Putra (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
Digital transformation has compelled media companies to reshape their business models, work culture, and organizational identity to remain relevant within algorithm-driven social media ecosystems. This study aims to analyse the internal communication strategies of PT Pantau Sumber Berita in managing its identity transformation from an online news portal into a digital platform-based content creator organization. The research employed a qualitative single case study approach, utilizing in-depth interviews, observation, and internal document analysis. The findings reveal that successful transformation was determined by the effectiveness of internal communication across three stages of organizational change: unfreezing, through building urgency and deconstructing the previous journalistic identity; moving, through sense-giving, dialogic communication, and work culture adaptation; and refreezing, through the institutionalization of a new identity based on KPI systems, . Furthermore, the study identifies resistance rooted in identity ambiguity, increased workload, and the inherent tension between journalistic depth and algorithmic demands for brevity and engagement, . The implications suggest that internal communication serves as a core strategic mechanism in media transformation by functioning as an arena for identity negotiation and sustainable cultural reconstruction.